Phase 1/2a, open‐label, multicenter study of RM‐1929 photoimmunotherapy in patients with locoregional, recurrent head and neck squamous cell carcinoma. Issue 12 (9th October 2021) - Cognetti, David M.; Johnson, Jennifer M.; Curry, Joseph M.; Kochuparambil, Samith T.; McDonald, Darren; Mott, Frank; Fidler, Mary J.; Stenson, Kerstin; Vasan, Nilesh R.; Razaq, Mohammad A.; Campana, John; Ha, Patrick; et al.
Abstract: Background: Recurrent head and neck squamous cell carcinoma (rHNSCC) represents a significant global health burden with an unmet medical need. In this study we determined the safety and efficacy of RM‐1929 photoimmunotherapy in patients with heavily pretreated rHNSCC. Methods: RM‐1929 (anti‐EGFR–IR700 dye conjugate) was infused, followed by tumor illumination. We evaluated safety, tumor response, and pharmacokinetics. Results: Nine patients were enrolled in Part 1 (dose‐finding) and 30 patients in Part 2 (safety and efficacy). No dose‐limiting toxicities were experienced in Part 1; 640 mg/m 2 with fixed light dose (50 J/cm 2 or 100 J/cm) was recommended for Part 2. Adverse events (AEs) in Part 2 were mostly mild to moderate but 19 (63.3%) patients had AE ≥Grade 3, including 3 (10.0%) with serious AEs leading to death (not treatment related). Efficacy in Part 2: unconfirmed objective response rate (ORR) 43.3% (95% CI 25.46%–62.57%); confirmed ORR 26.7% (95% CI 12.28%–45.89%); median overall survival 9.30 months (95% CI 5.16–16.92 months). Conclusions: Treatment was well tolerated. Responses and survival following RM‐1929 photoimmunotherapy in heavily pretreated patients with rHNSCC were clinically meaningful and warrant further investigation. Clinical Trial Information: NCT02422979.